Two Walls Orbital Decompression pada Thyroid Eye Disease - Efendi, Mardijas; Irfandy, Dolly; Primasakti, Pattih (Jurnal Kesehatan Andalas, 2024)
A patients with Grave Ophthalmopathy who underwent orbital decompression surgery involving two walls, medial and lateral. The surgery was performed in collaboration with an ENT specialist. This case report described a patient who presented with Thyroid Eye Disease NOSPEC V. It has been reported that a 35-year-old male had complained of bilateral proptosis, decreased visual acuity, and eye pain. The patient had been diagnosed with hyperthyroid 1 year before coming to the eye clinic. The patient was given a peribulbar steroid injection, but no improvement was observed. Visual acuity of the right eye was 3/60 and the left eye was 1/60. Lagophthalmos were seen on both eyes, 6mm in the right and 4mm in the left. The cornea of the right eye had infiltrated due to exposure keratitis. Proper eye movement was restricted to superonasal. The patient underwent medial and lateral orbital wall decompression of the left eye. Left eye visual acuity was improved to 20/150. Lagophthalmos was improved up to 3 mm. Medial and lateral orbital wall decompression are minimally invasive procedures involving removing a small portion of the bone from either the medial or lateral wall of the orbit. This allows more space for the eye to move backward, reducing pressure on the optic nerve and improving vision. This procedure also improves the cosmetic appearance of the eye. The ophthalmologic specialist performed the lateral wall decompression, and the ENT specialist performed the medial wall decompression. Medial and lateral orbital wall decompression has proven to be effective in treating patients with proptosis. The procedures have a low complication rate, and patients typically experience a significant improvement in their symptoms within a few weeks of the surgery.  Keywords:  orbital decompression, trans endoscopic decompression, thyroid eye disease